Changes in the Prevalence of Infection in Pregnant Women during the COVID-19 Lockdown - Dominique E. Werter; Heleen J. Schuster; Caroline Schneeberger; Eva Pajkrt; Christianne J. M. de Groot; Elisabeth van Leeuwen; Brenda M. Kazemier (Microorganisms, 2023)
Background: During the outbreak of SARS-CoV-2, strict mitigation measures and national lockdowns were implemented. Our objective was to investigate to what extent the prevalence of some infections in pregnancy was altered during different periods of the COVID-19 pandemic. Methods: This was a single centre retrospective cohort study conducted in the Netherlands on data collected from electronic patient files of pregnant women from January 2017 to February 2021. We identified three time periods with different strictness of mitigation measures: the first and second lockdown were relatively strict; the inter-lockdown period was less strict. The prevalence of the different infections (Group B Streptococcus (GBS)-carriage, urinary tract infections and Cytomegalovirus infection) during the lockdown was compared to the same time periods in previous years (2017–2019). Results: In the first lockdown, there was a significant decrease in GBS-carriage (19.5% in 2017–2019 vs. 9.1% in 2020; p = 0.02). In the period following the first lockdown and during the second, no differences in prevalence were found. There was a trend towards an increase in positive Cytomegalovirus IgM during the inter-lockdown period (4.9% in 2017–2019 vs. 12.8% in 2020; p = 0.09), but this did not reach statistical significance. The number of positive urine cultures did not significantly change during the study period. Conclusions: During the first lockdown there was a reduction in GBS-carriage; further studies are warranted to look into the reason why.